2019
DOI: 10.1101/575522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single and population coding of taste in the gustatory-cortex of awake mice

Abstract: A great deal is known about the broad coding and neural ensemble dynamics characterizing forebrain taste processing in awake rats, and about the relationship between these firing rate dynamics and behavior. With regard to mice, in contrast, data concerning cortical taste coding are few, inconclusive, and largely restricted to imaging, which lacks the temporal sensitivity necessary for evaluation of fast response dynamics. Here we have recorded the spiking activity of ensembles of gustatory cortical (GC) single… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 55 publications
15
44
0
Order By: Relevance
“…Though largely consistent, the observed responses to taste qualities (19-25%), cue (6-10%), and licking (~5%) were relatively sparse compared with previous work [20,27,28]. This discrepancy could arise from several factors.…”
Section: Multimodal Responses In Gcsupporting
confidence: 63%
“…Though largely consistent, the observed responses to taste qualities (19-25%), cue (6-10%), and licking (~5%) were relatively sparse compared with previous work [20,27,28]. This discrepancy could arise from several factors.…”
Section: Multimodal Responses In Gcsupporting
confidence: 63%
“…Most significantly, our results were in agreement with the conclusions reached in recent studies in which gustatory stimuli were delivered directly into the oral cavity. In fact, both in-vivo calcium imaging (Fletcher et al 2017;Livneh et al 2017) and electrophysiological recordings from awake mice (Levitan et al 2019) have indicated that a substantial fraction of GC neurons are modulated by gustatory stimuli and are likely to respond in a broadly tuned manner.…”
Section: Chemosensory and Palatability Neurons In The Gc Of Active LImentioning
confidence: 99%
“…Although a considerable amount of studies have investigated either spatial features of cortical taste-evoked activity in-vivo (Chen et al 2011;Fletcher et al 2017;Lavi et al 2018;Livneh et al 2017) or taste behavior (Graham et al 2014;Peng et al 2015), limited information is available on cortical taste electrophysiology in awake mice. One recent study described how GC neurons encoded gustatory information when taste stimuli were injected into the mouths of alert mice via intraoral cannulas (IOCs) (Levitan et al 2019). While IOCs provide a reliable and rapid method to deliver taste solutions, they add a degree of passivity to taste delivery and could potentially alter the sequence of events associated with the neural processing of gustatory information (Roussin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The third epoch (palatability) begins about a second after stimulus delivery and relates to the processing of taste palatability. This coding scheme has been further refined through trial-by-trial ensemble analyses and has been extensively validated by experimental evidence in rats and mice [6, 7, 16, 29, 30]. Alas, one of the limitations of this model has been its exclusive reliance on experiments in which rodents consume tastants that are flushed directly into the oral cavity through a surgically implanted intraoral cannula.…”
Section: Discussionmentioning
confidence: 99%